АNALYSIS OF INFORMATION CODING ALGORITHMS FOR PROTECTION OF PERSONAL DATA (Modern information system and technologies, 2018)
The basic, kryptoperidinium regarding the mechanisms of protection of personal information. The analysis of the mechanisms for the protection of personal data with obligatory comparison of them. The main difference between block ciphers and stream marked features of hash functions. Describes mechanisms used to implement the hash function SHA-256, it is determined that the SHA-256 algorithm is more stable and provides a sufficient degree of protection of any important information. Keywords. cryptomemetic, protection of personal data, algorithm, encoding, hash function, encryption, security.